Transformasi TRANSFORMASI SEMANGKA DESA LOMBANG: DARI BUAH SEGAR HINGGA PRODUK EKONOMIS INOVATIF BERBASIS ZERO WASTE: TRANSFORMASI SEMANGKA DESA LOMBANG: DARI BUAH SEGAR HINGGA PRODUK EKONOMIS INOVATIF BERBASIS ZERO WASTE - Desa Lombang, KKN Posko 15 (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2025)
This Community Service Program (KKN) aims to optimize the local potential of Lombang Village through the innovation of processing watermelon into economically valuable products using a Zero Waste approach. Watermelon is one of the village's leading agricultural commodities, yet often the harvest is not optimally absorbed by the market. Therefore, the KKN team from Annuqayah University, Post 15, initiated training and mentoring programs for processing watermelon into various products such as watermelon jam, candied watermelon rind, watermelon rind chips, and liquid organic fertilizer (LOF), by utilizing all parts of the fruit to reduce waste. This activity involved active community participation and aimed to raise awareness about organic waste management and empower family economies. The results showed that the community was very enthusiastic and capable of independently replicating the products. This program is expected to be an initial step towards economic independence based on local potential and environmentally friendly principles. Through mentoring activities for local residents especially mothers as part of the KKN program, followed by processing and production, this initiative also included training programs for the community on processing techniques and effective packaging. As a result, the comprehensive utilization of watermelon not only succeeded in reducing waste but also increased the economic value for the people of Lombang Village.